(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Breast cancer remains the most prevalent malignancy among women worldwide, accounting for a significant proportion of cancer-related morbidity and mortality. Despite substantial advances in oncology, survival outcomes continue to depend heavily on early detection and molecular profiling of tumors. Early screening methods such as mammography, ultrasound, and MRI have significantly improved diagnostic accuracy and allowed detection at earlier, more treatable stages. In parallel, molecular biomarkers — including BRCA1/2, HER2, PIK3CA, TP53, and hormone receptor status (ER, PR) — have transformed breast cancer classification and management. These markers provide crucial insights into tumor aggressiveness, therapeutic responsiveness, and patient prognosis. Integrating molecular biomarker assessment with effective early detection strategies allows for precision oncology, leading to personalized treatment and improved survival rates. This review summarizes current research on early detection approaches and key molecular biomarkers in breast cancer, emphasizing their combined role in enhancing prognosis and tailoring patient-specific therapies.